Nanoplanktonic diatom rapidly alters sinking velocity via regulating lipid content and composition in response to changing nutrient concentrations - Zhang, Wei; Hao, Qiang; Zhu, Jie; Deng, Yangjie; Xi, Maonian; Cai, Yuming; Liu, Chenggang; Zhai, Hongchang; Le, Fengfeng (Frontiers in Marine Science, 2023)
Diatom sinking plays a crucial role in the global carbon cycle, accounting for approximately 40% of marine particulate organic carbon export. While oceanic models typically represent diatoms as microphytoplankton (> 20 μm), it is important to recognize that many diatoms fall into the categories of nanophytoplankton (2-20 μm) and picophytoplankton (< 2 μm). These smaller diatoms have also been found to significantly contribute to carbon export. However, our understanding of their sinking behavior and buoyancy regulation mechanisms remains limited. In this study, we investigate the sinking behavior of a nanoplanktonic diatom, Phaeodactylum tricornutum (P. tricornutum), which exhibits rapid changes in sinking behavior in response to varying nutrient concentrations. Our results demonstrate that a higher sinking rate is observed under phosphate limitation and depletion. Notably, in phosphate depletion, the sinking rate of P. tricornutum was 0.79 ± 0.03 m d-1, nearly three times that of the previously reported sinking rates for Skeletonema costatum, Ditylum brightwellii, and Chaetoceros gracile. Furthermore, during the first 6 h of phosphate spike, the sinking rate of P. tricornutum remained consistently high. After 12 h of phosphate spike, the sinking rate decreased to match that of the phosphate repletion phase, only to increase again over the next 12 hours due to phosphate depletion. This rapid sinking behavior contributes to carbon export and potentially allows diatoms to exploit nutrient-rich patches when encountering increased nutrient concentrations. We also observed a significant positive correlation (P< 0.001) between sinking rate and lipid content (R = 0.91) during the phosphate depletion and spike experiment. It appears that P. tricornutum regulates its sinking rate by increasing intracellular lipid content, particularly digalactosyldiacylglycerol, hexosyl ceramide, monogalactosyldiacylglycerol, and triglycerides. Additionally, P. tricornutum replaces phospholipids with more dense membrane sulfolipids, such as sulfoquinovosyldiacylglycerol under phosphate shortage. These findings shed light on the intricate relationship between nutrient availability, sinking behavior, and lipid composition in diatoms, providing insights into their adaptive strategies for carbon export and nutrient utilization.